Assessing the geographic scale of genetic population management with microsatellites and introns in the clam Ruditapes decussatus. Issue 10 (15th April 2016) - Arias‐Pérez, Alberto; Cordero, David; Borrell, Yaisel; Sánchez, Jose Antonio; Blanco, Gloria; Freire, Ruth; Insua, Ana; Saavedra, Carlos
Abstract: The clam Ruditapes decussatus is commercially important in southwestern Europe, suffering from population decline and hybridization with exotic Manila clam ( R. philippinarum ). Previous studies with intronic markers showed a genetic subdivision of the species in three races (Atlantic, West Mediterranean, and Adriatic‐Aegean). However, detailed population genetic studies to help management of the main production areas in the southwest of Europe are missing. We have analyzed eight Atlantic and two Mediterranean populations from the Spanish coasts using 14 microsatellites and six intronic markers. Microsatellites confirmed the Atlantic and West Mediterranean races detected with introns and showed that genetic variability was higher in Mediterranean than in Atlantic populations. Both marker types showed that genetic differentiation of Atlantic populations was low and indicated that populations could be managed at the regional level in the case of Cantabrian and Gulf of Cadiz areas, but not in the case of Rias Baixas and the Mediterranean. This study shows the interest of including different types of markers in studies of genetic population structure of marine organisms. Abstract : The clam Ruditapes decussatus is a commercial species from the northwestern Atlantic and the Mediterranean that is facing population decline and hybridization with the introduced Manila clam. To help in genetic population management, we have conducted a population survey with microsatellites and intron RFLP markers. A regional pattern of population subdivision in the Atlantic has been found.